2012
DOI: 10.1016/j.conbuildmat.2012.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Corn cob lightweight concrete for non-structural applications

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. a b s t r a c tA lightweight concrete using granulated corn cob (without corn) as an aggregate is proposed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 9 publications
1
33
0
2
Order By: Relevance
“…At the same time, granulate of corn cob has also been suggested as a possible organic lightweight aggregate of concrete for non-structural applications, and as an alternative solution to currently applied solutions such as expanded clay, particles of expanded polystyrene (EPS), particles of cork or other lignocelluloses wastes (10). High level of water absorption of the granulate of corn cob, slow drying process and low compressive strength of the lightweight concrete produced were the main identified material limitations in (10). Taking into account the relevance of this type of building element, several research works (11)(12)(13)(14) have proposed alternative lightweight aggregates (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, granulate of corn cob has also been suggested as a possible organic lightweight aggregate of concrete for non-structural applications, and as an alternative solution to currently applied solutions such as expanded clay, particles of expanded polystyrene (EPS), particles of cork or other lignocelluloses wastes (10). High level of water absorption of the granulate of corn cob, slow drying process and low compressive strength of the lightweight concrete produced were the main identified material limitations in (10). Taking into account the relevance of this type of building element, several research works (11)(12)(13)(14) have proposed alternative lightweight aggregates (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A lightweight concrete for nonstructural purposes based on granulated corncob was studied and proposed [21] (case study II). A weight ratio of 6:1:1 [i.e.…”
Section: Case Study II -Lightweight Concrete For Nonstructural Purposmentioning
confidence: 99%
“…details I and II; Figure 14) to estimate the thermal transmission coefficient (U). Based on these experimental results and applying Expression (1), the U value of the lightweight concrete for nonstructural purposes based on corncob aggregate was possible to quantify and the respective value was 1.99 W/m 2°C [21].…”
Section: Case Study II -Lightweight Concrete For Nonstructural Purposmentioning
confidence: 99%
“…Shelter is one of the basic needs of human being. United Nations Center for Human Settlements estimates indicated that, more than half of the urban populations in developing countries live in life and health threatening conditions [1]. Unless dramatic and determined efforts are made on the housing front, trends and estimates point out that the situation is likely to become even worse.…”
Section: Introductionmentioning
confidence: 99%
“…Study conducted by M. Nisnevich et al [8] shows, using coal ash as replacement of cement makes concrete lightweight. Other materials like incenerator bottom ash [7], Sludge ash [9], Corn Cob ash [1] and the like are possible pozolanic materials that can be used for production of lightweight concrete.…”
Section: Introductionmentioning
confidence: 99%